Potential synergism between Beauveria bassiana and ether-extract of Ginkgo biloba for control of the two-spotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae) - Farzaneh Sadat Seyed-talebi; Paria Tork; Mohammad-Reza Dilmagani; Reza Talaei-Hassanloui (Journal of Crop Protection, 2012)
The entomopathogenic fungus Beauveria bassiana (Bals.) Vuill. is one of the important arthropod pathogens that can play an important role in the regulation of mite populations in agricultural ecosystems. In this study, the combined effect of a native isolate of fungus B. bassiana (EUT105) and ether-extract of plant, Ginkgo biloba was evaluated against the two-spotted spider mite, Tetranychus urticae Koch. At first, effect of three concentrations 5, 10 and 20% of G. biloba was evaluated on B. bassiana conidial germination and mycelial growth. Then, potential synergism between B. bassiana and G. biloba was investigated in order to incorporate both in the control of this pest. Only the 20% concentration of plant extract had significantly inhibitive effect on germination and mycelial growth. The mortality of adult female T. urticae increased significantly when B. bassiana was applied with 5 and 10% concentrations of G. biloba extract. Hence, there is a synergistic effect between this native B. bassiana and ether-extract of G. biloba in controlling the two-spotted spider mite.